Platelet-Membrane-Camouflaged Zirconia Nanoparticles Inhibit the Invasion and Metastasis of Hela Cells - Shang, Yinghui; Wang, Qinghai; Li, Jian; Zhao, Qiangqiang; Huang, Xueyuan; Dong, Hang; Liu, Haiting; Gui, Rong; Nie, Xinmin (Frontiers in Chemistry, 2020)
Zirconia nanoparticles (ZrO2 NPs) are widely applied in the field of biomedicine. In this study, we constructed a nanoplatform of ZrO2 NPs coated with a platelet membrane (PLTm), named PLT@ZrO2. PLTm nanovesicles camouflage ZrO2 NPs, prevent nanoparticles from being cleared by macrophage, and target tumor sites. Compared to ZrO2 alone, PLT@ZrO2 is better at inhibiting the invasion and metastasis of Hela cells in vitro and in vivo. In vitro, PLT@ZrO2 inhibited the growth and proliferation of Hela cells. Scratch-wound healing recovery assay demonstrated that PLT@ZrO2 inhibited Hela cells migration. Transwell migration and invasion assays showed that PLT@ZrO2 inhibited Hela cells migration and invasion. In vivo, PLT@ZrO2 inhibited the tumor growth of Xenograft mice and inhibited the lung and liver metastasis of Hela cells. Immunofluorescence and Western blotting results showed that anti-metastasis protein (E-cadherin) was upregulated and pro-metastasis proteins (N-cadherin, Smad4, Vimentin, E-cadherin,β-catenin, Fibronectin, Snail, Slug, MMP2, Smad2) were down-regulated. Our study indicated that PLT@ZrO2 significantly inhibits tumor growth, invasion and metastasis.